Perancangan Aplikasi Penjualan Pada Toko Sodaqo Ar-Ridho - Astalia Putri Yuniasih; Raudhatul Zannah; Umirah; Thoyyibah. T (CV. Multi Kreasi Media, 2023)
At this time the business of selling goods in Indonesia has developed quite well. Most of the sales of these goods have implemented the concept of online sales in their business, but the transaction services and information provided regarding the goods being sold are still very minimal. So far, sales at the Sodaqo Ar-Ridho Store have only relied on customers who come to the store, then they will shop, pay, and then the transaction is complete. In order to increase sales, an application is needed that supports the sales process. So, we created an application that will be used to make it easier for people to provide the goods they need. Sales and purchasing information systems will be more effective and efficient with proper computerization. Sales and purchasing information systems are able to provide speed of service, accurate data processing, so that data can be directly used and reported to superiors. The application design research method used is the waterfall method, where work on a system is carried out sequentially or linearly. Based on the test results it can be concluded that the software is as expected, meets user needs and is error free so it is feasible to use. With this application, it can minimize payment time, making it easier for buyers to make purchases without having to come to the store.